Legal Protection for Child Victims of Sexual Violence at the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) in Cirebon City - Sugiono, Sugiono; Tri Bawono, Bambang (UNISSULA Semarang, 2025)
Abstract. The attention of the Indonesian state towards children and the handling of children's problems is indeed very clear. This can be seen in the constitutional basis as stated in the 1945 Constitution. Then other regulations were born as a form of concern for children. Among them; Law No. 35 of 2014 concerning amendments to Law No. 23 of 2002 concerning child protection, which emphasizes the need for increased criminal sanctions and fines for perpetrators of crimes against children, especially sexual crimes, which aim to provide a deterrent effect, as well as encourage concrete steps to restore the physical, psychological and social health of children. To compensate for the suffering caused by sexual violence, the government has issued a policy for children who are victims of sexual violence as regulated in Government Regulation Number 43 of 2017 concerning the Implementation of Restitution for Children Who Are Victims of Criminal Acts. In addition, more specifically through the Regulation of the Minister of Women's Empowerment and Child Protection Number 1 of 2010 concerning Minimum Service Standards for Integrated Services for Women and Children Victims of Violence, which states that local governments are responsible for providing services and facilities for women and children who are victims of violence. As a manifestation of this regulation, each region has the authority and responsibility to provide facilities and services for victims of sexual violence. Sexual violence that occurs in Cirebon City, West Java is currently very horrific, according to the National Commission for Child Protection, Cirebon City is now in an emergency for sexual crimes against children. With the series and high number of sexual crimes in the Cirebon area, it is not an exaggeration if Cirebon is included in the category of emergency for sexual crimes against children after Bekasi and Tangerang.